University 3.0 as a Corporate Entity of Knowledge Economy: Models and Missions - Karpov, Alexander O. (International Journal of Economics and Financial Issues, 2016)
The University 3.0 is established in higher education systems in developed countries, performing social missions of education, research, and knowledge commercialization. The purpose of the article is the study of the University 3.0 as a corporate entity of knowledge economy. For this purpose the author discloses the content its fundamental social and economic missions and models in the context of social reality and management policy; gives examples of scientific studies of the University 3.0 challenges. Based on the analysis of social reality it is shown that strategic systems of social development conceptualizations – «New Public Management», «Network Governance», «Neo-Weberian State» – demonstrate basic transformations from which the University 3.0 takes its origin. The University 3.0 is built on the basis of interrelated models of network, creative, innovative and entrepreneurial universities. The University 3.0 is becoming the basis for global competitiveness of national economies and geopolitical alliances. Keywords: University 3.0; economy; research; commercialization; knowledge. JEL Classifications: I22, I23, I24, I25